ONLINE ARBITRATION MODEL FOR RUSSIA BASED ON INTERNATIONAL PRACTICE OF DISPUTE RESOLUTION IN E-COMMERCE - Shaydullina, Venera (Revista Inclusiones, 2020)
This study aimed to analyze the foreign practice of using different dispute resolution mechanisms in the field of electronic commerce in order to identify their disadvantages and advantages. The development of the commodity market and the services market in the digital era makes this study relevant and builds the need to develop a concept of online arbitration for Russia. Given the rapid growth of e-commerce, it is especially important to study consumer protection instruments, including with the use of digital technologies. This study applied an interdisciplinary approach and resorted to such methods of scientific cognition as historical, comparative, logical and legalistic, in the field of ecommerce. The study materials included acts of international law, national legislation of different countries, judicial practices of different countries, papers and publications by authors who study the regulation of e-commerce and analyze the Internet-based dispute resolution instruments. This article presents an analysis of international acts regulating consumer protection in e-commerce, identifies the main advantages of these instruments and their impact on the national legislation in different countries. The Russian legislation in terms of regulation of alternative dispute resolution procedures was also analyzed. The business practices of dispute settlement that were implemented on some digital platforms were reviewed. The study identified the best practices for implementing online dispute resolution in e-commerce. The article proposes a concept of online arbitration was that can be implemented in e-commerce in the Russian Federation. The issues of compliance with the New York Convention have become more problematic in terms of the guarantee of equal opportunities to the disputing parties to participate in the case, and the proper notification of the parties about the arbitration and the appointment of an arbitrator.